Community service to improve the comprehension of investment literacy for employees in Bogor City - Peter, Peter; Iskandar, Dini; Herlina, Herlina; Martalena, Martalena; Wahyusaputra, Tedy; Hadianto, Bram (LPPM Universitas Jenderal Achmad Yani, 2024)
This community service intends to enhance people's understanding of investment literacy amid fraudulent investments. The people intended are employees and affiliated persons of BPK Penabur in Bogor City. Moreover, the service community team uses the lecture method to train the participants, the advanced questions to assess their investment knowledge level, and the pair sample t-test to detect the difference of precise correct responses to measure the effectiveness of this event. Based on the evaluation, the team reports that their investment literacy level elevates before and after the training sections, reflected by 62.83% to 78.95% correct responses, which is they have the middle level based on the certain criteria. Having this level, they are suggested to start investing in bonds, shares, and mutual funds by contacting the local securities companies or following the financial certification provided by Maranatha Christian University to get comprehensive economic knowledge.